Diamond Raman oscillator operating at 1178 nm - Heinzig, Matthias; Palma-Vega, Gonzalo; Walbaum, Till; Schreiber, Thomas; Eberhardt, Ramona; Tuennermann, Andreas (Optics Letters, 2020)
In this contribution, we report high-power Raman frequency downconversion based on an Yb-doped fiber amplifier and a linear external diamond Raman cavity. A maximum output power of 136 W with nearly diffraction-limited beam quality was achieved by pumping in quasi-continuous-wave mode with 10% duty cycle and 10 ms on-time duration. For continuous-wave operation, we achieved record average power of 46 W centered at 1178 nm. The emergence of stimulated Brillouin scattering in diamond is further investigated. This technology shows the potential to extend the spectral range of fiber lasers to reach uncommon wavelengths at high power levels.
CRIS-Team Scopus Importer:2023-04-20